Interview with Prof. Piet Meiring - M Laubscher (Acta Theologica)
Professor Piet Meiring was born in Johannesburg in 1941. He studied at the University of Pretoria, and at the Free University, Amsterdam. He was ordained to the ministry of the Dutch Reformed Church (DRC) in 1968 and served in three congregations in Pretoria. His academic career includes the chair in Missiology and Church History, University of the North (Turfloop); a parttime lectureship at the University of South Africa.